Shi jie xiang xiang xi xue dong jian yu Ming Qing Han wen di li wen xian = Imagination of the world : the eastward reflections of western learning and Chinese geographical documents in the Ming ang Qing dynasties - Zou, Zhenhuan 1957- (Guo jia she ke ji jin hou qi zi zhu xiang mu, 2022)
Abstract